The territoriality, the memory and the therritory from the process of patrimonialization of the historical center of Manizales: The contradiction within the every day the institutional. - Botero Escobar, María (2021)
The historic center of Manizales is a crucial point of reference to understand, to a large extent, the existing imaginary within the city, since this, historically, was the setting where the foundation and location of the city took place, but it has also been the landscape on which countless milestones and historical periods have occurred. That is why, the main objective of the research is to analyze the way in which the Manizales residents perceive their territory in the historic center under different temporalities that respond to historical, economic, social and political events that construct reality. It is intended to define diachronically the social, patrimonial, symbolic and daily construction of the historic center of Manizales, articulating all these elements under the concept of territoriality, memory around the territory, since, in this, the key will be found to define historical processes, collective, legislative and institutional that will be the navigation chart of this investigation. This research contributes to identifying the social dynamics that are built over time around the historic center of Manizales both from the institutional point of view and from the daily life where relationships are established from the territoriality that transcend spatial dimensions.